Reconciliation : A way of life for the world - Masango, Maake J. (Verbum et Ecclesia, 2005)
Paul seems to reserve the word "reconciliation" for use as the most powerful way of expressing the meaning of the life, death, and resurrection of Jesus Christ (see 2 Cor 5:18-19; Col 1:20, 22; Rom 5:10-11; 11:15; Eph 2:16). The main aim of reconciliation is to bring people together in such a way that they may begin to deal with their conflict in the midst of their tension (e.g. in South Africa).–C.R.M. Abstract Number: NTA50-2006-1-323
Free
Keywords: Epistles-Revelation – Paul.